2009
DOI: 10.1007/s11802-009-0161-2
|View full text |Cite
|
Sign up to set email alerts
|

Methods comparison for microsatellite marker development: Different isolation methods, different yield efficiency

Abstract: Microsatellite markers have become one kind of the most important molecular tools used in various researches. A large number of microsatellite markers are required for the whole genome survey in the fields of molecular ecology, quantitative genetics and genomics. Therefore, it is extremely necessary to select several versatile, low-cost, efficient and time-and labor-saving methods to develop a large panel of microsatellite markers. In this study, we used Zhikong scallop (Chlamys farreri) as the target species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…With database mining, we ended up with 3 polymorphic markers out of 21 repetitive motif containing EST sequences (an efficiency of 14%). When considering the efficiency reported to the initial number of EST sequences screened, the efficiency drops to 0.16%, which is comparable with what other authors have found (Zhan et al, ). With the next generation sequencing of enriched libraries, we ended up with 10 markers out of 151 tested sequences (7% efficiency).…”
Section: Discussionsupporting
confidence: 90%
“…With database mining, we ended up with 3 polymorphic markers out of 21 repetitive motif containing EST sequences (an efficiency of 14%). When considering the efficiency reported to the initial number of EST sequences screened, the efficiency drops to 0.16%, which is comparable with what other authors have found (Zhan et al, ). With the next generation sequencing of enriched libraries, we ended up with 10 markers out of 151 tested sequences (7% efficiency).…”
Section: Discussionsupporting
confidence: 90%
“…They can detect a large number of alleles, with high repeatability and inter‐species transferability, and have mainly been used in the study of bio‐effective populations, genome identification, kinship and other issues, and have even been applied in medical research (Clauss et al, 2002; Turpeinen et al, 2001; Koch et al, 2009; Hiroshi et al, 2007; Zauber et al, 2003). Despite their global applicability, the development of microsatellites requires considerable technical effort to construct the rich microsatellite libraries, which can be expensive or time‐consuming, or the number of different types of useful microsatellite loci that are successfully obtained can be limited (Peakall et al, 1998; Castoe et al, 2010; Zhan et al, 2009). Recent advances in large‐scale RNA‐seq have provided a fast, cost‐effective and reliable way to generate large expression data sets in non‐model species (Lei et al, 2017; Bhandawat et al, 2016; Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular marker-assisted selection (MAS) is being widely employed in traditional selective breeding (Zhan et al, 2009;Sun et al, 2006). Polymorphism in human FSHβ associated with fertility suggests the possible effect of balancing selection (Grigorova et al, 2007).…”
Section: Discussionmentioning
confidence: 99%